2019
DOI: 10.1002/adfm.201908073
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Photothermal Efficacy by Simultaneous Intra‐ and Intermolecular Fluorescence Quenching

Abstract: Recently, using in situ self-assembly-induced fluorescence quenching (i.e., intermolecular quenching denoted herein) of a photothermal agent (PTA) to enhance its photothermal efficiency has proven to be a successful photothermal therapy (PTT) strategy. But to the best of current knowledge, using simultaneous intra-and intermolecular fluorescence quenching of a PTA to additionally increase its photothermal efficacy has not been reported. Herein, employing a click condensation reaction and a rationally designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 66 publications
1
40
0
Order By: Relevance
“…The concentration difference between normal tissue and tumor tissue can be generated, and the temperature of the tumor site can be selectively increased [ 15 ]. The ideal solution is to give PTAs a self-regulating photothermal conversion capability, which means that PTAs have a weak photothermal conversion ability in normal tissue but a strong photothermal conversion ability at the tumor site [ 13 , 14 , 16 ]. Theoretically, the temperature of the tumor site can be selectively increased, with minimal or no damage to normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration difference between normal tissue and tumor tissue can be generated, and the temperature of the tumor site can be selectively increased [ 15 ]. The ideal solution is to give PTAs a self-regulating photothermal conversion capability, which means that PTAs have a weak photothermal conversion ability in normal tissue but a strong photothermal conversion ability at the tumor site [ 13 , 14 , 16 ]. Theoretically, the temperature of the tumor site can be selectively increased, with minimal or no damage to normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we checked the photothermal conversion efficiency (η) of AuNP@1 + GSH + Furin, AuNP@1‐Scr + GSH + Furin, and AuNP by measuring their heating and cooling curves using previously reported methods (Figure S21, Supporting Information). [ 31 ] The calculated η value of AuNP@1 + GSH + Furin was 3.02%, higher than those of both AuNP@1‐Scr + GSH + Furin (η = 2.99%) and AuNP (η = 1.39%). Above results well confirmed that furin‐instructed aggregation of AuNP@1 enhanced the photothermal properties of gold nanoparticles.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, SASMs, being generated by a specific enzymatic reaction, are also able to interact with multiple targets or to disrupt multiple pathways in cancer cells, 43 which makes SASMs attractive molecular entities for killing cancer cells effectively, reducing side effects, and minimizing MDR in cancer therapy. 44,45 …”
Section: Sasms Inhibit Pathogenic Cellsmentioning
confidence: 99%